Evaluating Preference and Performance in Accumulated versus Distributed Response–Reinforcer Arrangements. Issue 6 (November 2020) - Weston, Regan; Davis, Tonya; Ross, Robert K.
To determine the effects of response–reinforcer arrangements on task performance and preference, participants completed tasks on accumulated and distributed response–reinforcer arrangements. Three males diagnosed with an autism spectrum disorder completed tasks before receiving 5-min or 30-seconds access to a preferred stimulus. To enhance discrimination between the two arrangements, color-coded token boards were used to represent each arrangement. Responding was evaluated within a multielement design to compare the response rate across conditions for each participant. A preference assessment was conducted after the comparison to determine whether a preference for one of the arrangements emerged. All participants produced a higher rate of responding in the accumulated schedule of reinforcement.